ANALISIS KEBERLANJUTAN DESA WISATA (STUDI KASUS DESA WISATA SEPAKUNG, KECAMATAN BANYUBIRU, KABUPATEN SEMARANG) - Hafida, Siti Hadiyati Nur; Dewi, Ratih Puspita; kesumaningtyas, mayang arum; Nastiti, Bening Ati; Puspitasari, Windy; Masruroh, Laila; Meliani, Meliani; Satria, Alviedo Bagoes; Ali, Fierda Abdullah; Bima, Dadang Surya (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2019)
Tourism sustainability is a process to determine the impact and implementation of prevention in tourism activity. The potential tourism is rural tourism. In rural tourism, development will be very helpful in improving the economy and welfare of the community. Communities become active manage in participating rural tourism to boost the economy and their own welfare. Tourism activities will appreciate the potential of local and community-based resources. It is with such considerations in anticipation of changes in land ownership, social structure, and culture. One of the rural tourism in Indonesia is the Sepakung Village, that located in Banyubiru, Semarang District. This study used a quantitative research. This study was conducted to determine the sustainability of Sepakung based on the ecological, economic, and social dimensions. Collecting data using random sampling with 100 respondents. Sustainability analysis using Multi-Dimensional Scaling (MDS) in Rapfish method. The results showed that the sustainability of the ecological, economic, and social dimensions have higher indeks, that is 80.8; 70.3 and 98.9. Need a cooperation between communities, village government and private organization to develop rural tourism so, the management in rural tourism will be good and can help the community to improve their welfare.